Skim coating / Muhammad Asyraf Othman - Othman, Muhammad Asyraf (Universiti Teknologi MARA, Perak, 2021)
Skim Coating is one of the additional value after the plastering process, therefore, skim coating can be used to smoothen the wall or to repair the drywall. This report will track down the method of skim coating that were conducted in Ibai Golf and Country Resort Kuala Terengganu for Double Storey Bungalow for Bmi Construction Sdn Bhd . The objective of the report is to identify the factors that should be considered in skim coating, the method of skim coating, and the problem of skim coating. It will focus on the type, advantages and disadvantages of the skim coating that is used for the case study, the material and the tools that are used for the skim coating. In this report, it also shows the details, step by step of skim coating procedure from scratch.